DESIGNING CIRCUITS BASIC INPUT WITH PPI BROKERAGE 8255 USING C LANGUAGE - Ryan Adtrianshah Akbar; Nenny Anggraini, SKom, MT (Jurnal Sistem Komputer, 2006)
Series "Designing circuits Basic Input With PPI 8255 Intermediary Language Using C", is a series composed of PCs, interface 8255, and a series of basic input modules that are interconnected with one another. 8255 PPI servesto mediate between the computer with a basic set of inputs. This circuit is used to enter data in the form of binary numbers and output can then be viewed on a computer screen in the form of decimals. For data processing in this circuit using the languageC.